The Continuation of Violence in the Eastern Democratic Republic of the Congo: A Consequence of Low State Capacity - Stevens, McKenzie (Colloquium: The Political Science Journal of Boston College, 2021)
The enduring conflict in the Democratic Republic of Congo is rooted in the state’s colonial legacy, the predatory rule of its past leaders, and the outbreak of the African World War which has rendered the DRC’s eastern regions extremely unstable. The conflict has persisted due to the low state capacity of the DRC government which has failed to mitigate the devastation faced by its people and has even been a perpetrator of violence directed towards civilians. The DRC’s ineffective military, rampant poverty, and repression of civil liberties have left the Congolese people in a state of desperation, with some joining rebel groups to gain relief. For a conclusive cessation of the violence in eastern DRC to occur, comprehensive democratic reforms that increase the accountability of the government and enable the people to directly influence politics must be established within the state’s political systems.